2020
DOI: 10.1016/j.jasrep.2020.102351
|View full text |Cite
|
Sign up to set email alerts
|

Locational preferences and spatial arrangement in the barrow landscape of Serra do Barbanza (North-western Iberia)

Abstract: As anywhere else, GIS is an essential tool in Galician archaeological research for examining and analysing spatial data. This is something quite clear in megalithic studies where in the last years these methods have been used for contrasting hypotheses regarding locational preferences drawn from fieldwork. As such, in this paper, a study of locational patterns of the megalithic sites located in the flattened top territories of A Serra do Barbanza (Galicia, NW Spain) is carried out. Using a site-predictive mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
0
5
0
5
Order By: Relevance
“…This trend had already been detected in previous approaches using predictive modelling and GIS platforms. In these studies, it was observed that visual prominence was a significant predictor for mounds in the Barbanza (CaRReRo-Pazos et al, 2020), but not for rock art sites (RodRíguez and FábRegas, 2015).…”
Section: Impact Of the Characteristics Of Monuments On Their Percepti...mentioning
confidence: 94%
See 1 more Smart Citation
“…This trend had already been detected in previous approaches using predictive modelling and GIS platforms. In these studies, it was observed that visual prominence was a significant predictor for mounds in the Barbanza (CaRReRo-Pazos et al, 2020), but not for rock art sites (RodRíguez and FábRegas, 2015).…”
Section: Impact Of the Characteristics Of Monuments On Their Percepti...mentioning
confidence: 94%
“…The relevance of Landscape Archaeology among Galician researchers (CRiado, 1989;CRiado and VilloCh, 1998), combined with the huge impact of foreign scholars doing fieldwork there (bRadley, 1997;bRadley, CRiado and FábRegas, 1994), has led to the production -from the 1980s onwards-of many studies exploring the distribution of mounds and petroglyphs across the region. In most of these approaches, prehistoric monuments have been interpreted as nodes connected to each other through routes retraceable by means of field work (CRiado and VilloCh, 2000), the analysis of mobility patterns of animals (inFante, VaqueRo and CRiado, 1992), the layout of historical routes (PaRCeRo, CRiado and santos,1998) and -in recent years-through the calculation of least-cost paths using GIS tools (CaRReRo-Pazos, beVan and lake, 2019; CaRReRo-Pazos et al, 2020;FábRega-álVaRez and PaRCeRo-oubiña, 2007;RodRíguez and FábRegas, 2015;RodRíguez-Rellán and FábRegas, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…CriadO bOadO, 1988). Un trabajo que fue continuado y completado posteriormente con la adenda de otros factores, caso de la proximidad de los monumentos a zonas de ruptura de cuenca hidrográfica (CarrerO-pazOs et al, 2020). Todo ello parece indicar una suerte de «juego locacional», donde ciertamente la visibilidad y proximidad a rutas de tránsito son factores que parecen haber desempeñado un papel relevante en la configuración inicial de estos paisajes funerarios y monumentales.…”
Section: Caso De Estudio Los Túmulos Megalíticos De a Serra Do Barban...unclassified
“…No es descabellado pensar que podríamos estar ante un conjunto funerario y monumental con amplia temporalidad, algo esperable si observamos necrópolis tumulares y megalíticas bien conocidas como la de A Serra da Aboboreira, en Portugal (JOrge, 1991). Por último, no debemos olvidar que la distribución de monumentos tumulares y megalíticos de As Chans do Barbanza, que en la actualidad cuenta con 38 monumentos tras las investigaciones del Grupo de Estudios para la Prehistoria del Noroeste Ibérico, GEPN-AAT (barbeitO pOse et al, 2018;busteLO abuín et al, 2017;CarrerO-pazOs et al, 2020), puede no corresponderse con la existente en tiempos prehistóricos, habida cuenta de las múltiples destrucciones de monumentos sucedidas en tiempos históricos (atestiguadas en las fuentes escritas, cfr. martinón-tOrres, 2001), y aquellas otras que continúan sucediendo en la actualidad (cfr.…”
Section: Caso De Estudio Los Túmulos Megalíticos De a Serra Do Barban...unclassified
“…Furthermore, in Figure 3, it appears that the spatial distribution of the dolmens shows spatial clustering. There are various techniques to measure the intensity of points such as H function, L function, or the pair correlation function (Bevan et al, 2013; Carrero‐Pazos et al, 2020; Davis et al, 2020). Figure 4 shows the pair correlation function g obtained using the Ripley and Translate methods of estimation; also, the theoretical value of g (r) for the Poisson process (vector of values equal to 1) is displayed to identify the presence of clustering (values greater than 1) or dispersion (values less than 1).…”
Section: Spatial Statisticsmentioning
confidence: 99%